ATRIBUT CLEAT DAN HUBUNGANNYA TERHADAP KUALITAS DAN PERMEABILITAS BATUBARA DALAM KEGIATAN EKSPLORASI GAS METANA BATUBARA BLOK RENGAT, CEKUNGAN SUMATRA TENGAH - PRAHASTIWI, RINATRI
Central Sumatera basin is one of the biggest CBM reserved in Indonesia, unfortunately study about CBM in this Central Sumatra Basin are still minim, in studi for exploration or exploitation. As much of publication that have been published before about the different of conventional gas and methane gas as it fungsion as reservoir and source rock. The different are mostly as a cause of the characteristic and the origin of the coal (Laubach, 1998) that on study about methane gas and it relation to quality of the coal and its characteristic will give a new description of exploitation activity in the future. Using attribute cleat data, proximat analysis data and secondary data, showing that Blok Rengat, specifically at Lahat Formation and Muaraenim Formation having one dominant cleat orientation which is north – south. Influence of the local structure also occur minimize. The outcrop permeability showing of number 2.4-8.7 darcy, and the microcleat undersurface showing of number 0.1-2md at 263 depth. Maksimum and minimum value of attribute analysis of the cleat showing average value of density are variety from 12.92–0.035 cm/cm2, avarege of spasing 2.86–0.9 cm, average of aperture 17.22–10.33 cm, average of high 17.22–10.33 and value of intensity are 414–99. The correlation between coal quality showing that there a same pattern of adjusted ash and total moisture, these making identification that there other thing that are influence to the forming cleat process that have to be studied more.